2012
DOI: 10.1007/s10620-012-2188-2
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Associated with the Difficult-to-Sedate Endoscopy Patient?

Abstract: Pre-procedural state or trait anxiety is associated with difficult sedation during endoscopy. In this study neither alcohol abuse nor chronic opiate/BDZ use was associated with difficult sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
2
19
0
1
Order By: Relevance
“…Relatively little research has been done in identifying risk factors for difficult‐to‐sedate patients undergoing endoscopic procedures. One recent study involving 143 patients identified pre‐procedure anxiety and chronic psychotropic use as risk factors for patient undergoing moderate sedation with midazolam and fentanyl for OGD and colonoscopy, and found that gender, alcohol abuse, history of sexual abuse or physical abuse and chronic opioid or benzodiazepine use were not risk factors contrary to the investigators’ hypothesis . Another study that included 135 patients found that for patients undergoing deep sedation with propofol, pre‐procedure anxiety did not correlate with required anaesthesia dose .…”
Section: Discussionmentioning
confidence: 95%
“…Relatively little research has been done in identifying risk factors for difficult‐to‐sedate patients undergoing endoscopic procedures. One recent study involving 143 patients identified pre‐procedure anxiety and chronic psychotropic use as risk factors for patient undergoing moderate sedation with midazolam and fentanyl for OGD and colonoscopy, and found that gender, alcohol abuse, history of sexual abuse or physical abuse and chronic opioid or benzodiazepine use were not risk factors contrary to the investigators’ hypothesis . Another study that included 135 patients found that for patients undergoing deep sedation with propofol, pre‐procedure anxiety did not correlate with required anaesthesia dose .…”
Section: Discussionmentioning
confidence: 95%
“…[16][17][18] In previous studies, there has been some inconsistencies in the findings, such as the role and effect of gender, and prior use of certain medications such as benzodiazepines. [11][12][13] To better identify potential predictors, we decided to compare two groups of patients at opposite ends of the tolerance spectrum. By directly comparing patients that require a small amount of sedation to those that are difficult to sedate, our hope was that differences between these two populations would become more apparent and clear.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In another study where detailed information on patients' psychiatric and substance use history prior to endoscopy was collected, followed by an assessment of tolerance using the Richmond agitation sedation scale (RASS), gender had no effect on state and trait anxiety during endoscopy. 13 There has been similar disagreement on whether higher or lower BMI is a risk factor for poor tolerance. 11,12 Interestingly it has been suggested that ASA grading had no significant effect on patient tolerance.…”
Section: An Increasing Number Of Endoscopy Centres In the Unitedmentioning
confidence: 99%
“…A total of 80 individuals who signed the agreement were recruited among those undergoing ESD for gastric neoplasms under monitored anesthesia care. Exclusion criteria were: (i) patients aged <20 years or >80 years; (ii) patients with American Society of Anesthesiologists (ASA) Physical Status Classification III–IV; (iii) pregnancy or lactation; (iv) a history of alcohol consumption or drug abuse; (v) allergy to any of the drugs used in this study, such as MDZ, DEX and opioids; and (vi) those who refused to sign the consent form and with serious psychiatric problems . The first ESD procedure was included only when the procedure had been performed more than twice within the study period.…”
Section: Methodsmentioning
confidence: 99%